Determinants of stunting, wasting, and underweight in five high-burden pockets of four Indian states - Rajesh Kumar Sinha; Richa Dua; Vasundhara Bijalwan; Shivani Rohatgi; Praveen Kumar (Wolters Kluwer Medknow Publications, 2018)
Objectives: Prevalence of under-nutrition is very high in India. Under-nutrition is a result of interplay between different immediate, underlying, and basic causes. The study was conducted with the objective to identify significant predictors of stunting, wasting, and underweight. Methods: Cross-sectional studies with 2299 children from five high-burden pockets of four Indian states were conducted. Primary data on their anthropometric measurements along with their households' demographic and socioeconomic characteristics were collected. Binary logistic regression analyses were performed to examine the predictors of stunting, wasting, and underweight. Results: Results show very high prevalence of stunting, wasting, and underweight in all five regions covered in the study. Multivariate analyses show that food security, use of toilets, and low body mass index status of mothers were the major predictors of stunting and underweight among children. Acute respiratory infection disease was the major predictor of underweight and diarrhea was the major predictor of stunting. Younger children (<24 months) had lower odds of underweight and stunting compared to older children (24-59 months). The analyses showed higher odds of wasting among male children. Regional variations were also seen in the study with higher odds of underweight and wasting in Khuntpani block and higher odds of stunting in Naraini block. Conclusion: The above findings indicate that for comprehensively addressing child under-nutrition, it is very important to address maternal nutrition, improve food security, and reduce poverty status, provide better water and sanitation facility to the community, control infections, and address regional disparity.